Resistência à corrosão das fases presentes em amálgamas dentários - Acciari, Heloísa Andréa [UNESP] (2001)
In this work, the corrosion resistance behavior of three of their phases presents in dental amalgam has been investigated: γ1-Ag2Hg3 (the matrix phase in the microstructure), γ2-Sn7-8Hg (the phase most susceptible to corrosion in the oral cavity, according to the literature) and Ag-Cu eutectic (the component of the more modern powder alloys, the objective being to reduce the quantity of γ2-Sn7-8Hg formed during the amalgamation and in this way increase its corrosion resistance). Electrochemical measurements were carried out in 0.9% aqueous sodium chloride in order to simulate the aggressivity of the oral cavity, using open circuit potential measurements, polarization curves and electrochemical impedance. The corrosion resistance exhibited by alloys can be associated with formation of a corrosion layer and seems to be dominated by the presence of the porous layer in the products surface.